Can rooted apical cuttings complement seed systems to improve availability of quality seed potato in Africa? – The case of Kenya - Wauters, P.; Hutchings, J.; Munguti, F.M.; Borus, D.; Nyawade, S.; Atieno, E.; Sharma, K.; Parker, M. (Wiley, 2024)
Limited availability and access to quality seed is a major challenge faced by the Kenyan potato subsector. Smallholder farmers cultivate the bulk of potato mainly planting seed from informal sources without any quality assurance which contributes to low yields. In recent years, private sector businesses have engaged in certified seed potato production with positive impact on the volumes available, relying on minitubers to multiply in the field over 3–4 generations. Rooted apical cuttings (RACs) provide a productive alternative starter material that can further boost the Kenyan seed systems. Stokman Rozen Kenya Ltd (SRK) is a private sector business that has embraced this technology in 2017. Also, small-scale nurseries have recently started the commercial production of cuttings. They both sell RACs mainly to seed growers for further bulking, but ware potato farmers can also produce quality seed on-farm for their own use from RACs when applying good agricultural practices. This paper examines the initial experiences of both SRK and small-scale nurseries in the production and marketing of RACs as well as their performance during subsequent field multiplications. Producing and selling RACs offers a profitable business opportunity, especially when productivity and sales increase. Compared to other rapid multiplication technologies, RACs also allow to significantly increase the volumes of early generation seed produced. Key recommendations are to create awareness and to develop adequate marketing strategies to promote their uptake, and to ensure RACs are adequately multiplied into commercial seed to improve its availability to smallholder farmers in Kenya.